Influence of epoxidized palm oil on polyhydroxyalkanoates tensile properties - Abdullah, Aida Ashikin; Hassan, Norita; Hassan, Noor Azlina (UR Publishers, 2018)
These papers focus on the influence of epoxidized palm oil (EPO) on polyhydroxyalkanoates (PHA) tensile properties. Previous researchers has found a thermoplastic polymer polyhydroxyalkanoates (PHA) that exhibit biodegradable properties and produced from renewable materials such as sugar and molasses. However, pure PHA are brittle materials. A modification on the mechanical properties of PHA can be done by introducing plasticizer to the materials. In this study, (EPO) was used as plasticizer to PHA with varied composition of EPO content range 1wt.% to 5 wt.%. The blend was prepared by mixing the two components using internal mixer at 175 °C. The mechanical property of each sample was determined by tensile test. Result shows that the Young’s modulus of PHA was improved with 3 wt.% optimum plasticizer loading while lowest tensile strength which indicates the rigidity of PHA/EPO at this composition is optimized.